Penerapan Media Edugames Jelajah Jawa Tengah Berbasis Articulate Storyline3 Terhadap Literasi Digital Abad 21 - Marifah, Maulina Zaidatul; Raharjo, Tri Joko; Yulianto, Arief; Subronto, Subronto (Jurnal Pendidikan Sultan Agung, 2024)
The low level of digital literacy of students in the 21st century has resulted in formative learning outcomes in science and science learning that are not in accordance with the criteria for achieving learning objectives (KKTP). The low formative learning outcomes are caused by students' lack of enthusiasm in learning science and technology. To overcome these problems, learning media are needed that are appropriate to the characteristics of students. The use of Edugames Media based on Articulate Storyline 3 is considered as one of the learning media that suits the characteristics of students in science learning. The aim of the research is to apply the application of edugames. The method used in research is R&D. The method used is to collect various relevant sources so as to obtain the essence of previous research and then analyze it. The research trial subjects were 4th grade students at SD Negeri 1 Gubug. The results of this research obtained validator results from media expert 1 with a percentage of 95% and media expert 2 with a percentage of 94%. And material expert validator with a percentage of 905% and e material expert 2 with a percentage of 89%. So it can be concluded that the application of articulate story line 3 based educational media is effective in science and science learning so that it has an effect on increasing digital literacy and improving students' cognitive learning outcomes which can be proven through the achievement of KKTM.